1999
DOI: 10.1002/(sici)1096-9926(199901)59:1<39::aid-tera9>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Candidate genes for nonsyndromic cleft lip and palate and maternal cigarette smoking and alcohol consumption: Evaluation of genotype-environment interactions from a population-based case-control study of orofacial clefts

Abstract: Previous studies suggest that the relationship between genes and nonsyndromic cleft lip ± cleft palate (CLP) or cleft palate only (CP) may be modified by the environment. Using data from a population‐based case‐control study, we examined allelic variants for three genes, i.e., transforming growth factor alpha (TGFA), transforming growth factor beta 3 (TGFB3), and Msh (Drosophila) homeobox homolog 1 (MSX1), and their interactions with two exposures during pregnancy (maternal cigarette smoking and alcohol consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
148
2
19

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(175 citation statements)
references
References 40 publications
6
148
2
19
Order By: Relevance
“…8,11,19,20 In the present research, no transmission distortion was found in the transmission disequilibrium analysis for either MSX1-CA or TGFB3-CA intragenic markers, but TGFB3-CA exhibited a trend to excess maternal transmission. Our findings suggest that both the maternal and fetal RR results are in agreement for both TGFB3-CA alleles, as the 163-bp allele had a deleterious recessive effect, whereas the 165-bp allele had a protective recessive effect.…”
Section: Discussioncontrasting
confidence: 49%
“…8,11,19,20 In the present research, no transmission distortion was found in the transmission disequilibrium analysis for either MSX1-CA or TGFB3-CA intragenic markers, but TGFB3-CA exhibited a trend to excess maternal transmission. Our findings suggest that both the maternal and fetal RR results are in agreement for both TGFB3-CA alleles, as the 163-bp allele had a deleterious recessive effect, whereas the 165-bp allele had a protective recessive effect.…”
Section: Discussioncontrasting
confidence: 49%
“…[31][32][33][34][35][36][37][38] Reports have classified oral clefts in many different ways, but nearly all have shown a positive association with maternal smoking, with only a few reports not observing this association, 14,39,40 and one report not observing this association for cleft palate alone. 34 The magnitude of the effect estimate observed in our study also is similar to that reported from the wide array of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…6,21,[39][40][41][42][43] Our results demonstrated that not only the Tgfβ-pathway genes but also other pathway-related genes might interact each other to regulate medial edge epithelium disintegration and complete palatogenesis (Supplementary Figure 2) In several studies, it has been suggested that there is a gene-environment interaction exists between smoking and TGFα expression for the induction of cleft palate. 8,25,[44][45][46][47][48][49] By using our microarray analysis and filtering cleft palate-related genes, we determined that nicotine is the highly susceptible element of smoking to induce down-regulation of TGFα, which may explain the palatal size abnormality observed in nicotine-treated pups. The presence of partial palatal seam in the newborn pups, which otherwise would have disintegrated at 14.5 to 16.5 dpc indicates: (1) the growth of the palate towards each other to form a seam, although in smaller size and shape, is not altered; (2) the genes that causes immaculate seam disintegration might have been effected by nicotine exposure.…”
Section: Discussionmentioning
confidence: 98%